YWHAG promotes bladder cancer metastasis by regulating TMOD3 to activate ERK1/2 and JNK phosphorylation in the MAPK pathway - Tai Tian; Shiming He; Han Hao; Bao Guan; Yanqing Gong; Jian Fan; Zhenpeng Zhu; Wenzhi Gao; Yucai Wu; Ninghan Feng; Aixiang Wang; Yuexian Guo; et al. (Journal of Translational Medicine)
Abstract Objective This study aims to investigate the molecular mechanisms by which YWHAG (Tyrosine 3-Monooxygenase/Tryptophan 5-Monooxygenase Activation Protein Gamma) promotes metastasis in bladder cancer. Specifically, it seeks to elucidate the role of YWHAG in driving cancer cell invasion and its potential as a prognostic marker for bladder cancer progression. Methods The expression pattern of YWHAG in both primary and metastatic bladder cancer tissues was analyzed using immunohistochemistry (IHC) to determine its correlation with clinical stage and prognosis in bladder cancer patients. The functional role of YWHAG in bladder cancer progression was examined through a series of in vitro and in vivo experiments. Transcriptome sequencing was employed to identify the key signaling pathways regulated by YWHAG. The interaction between YWHAG and TMOD3 (Tropomodulin 3) was confirmed through pull-down assays coupled with mass spectrometry, co-immunoprecipitation (Co-IP), and cell immunofluorescence studies. Finally, TMOD3 knockdown experiments were conducted to verify whether the pro-metastatic effects of YWHAG in bladder cancer are mediated through TMOD3. Results YWHAG expression was significantly elevated in metastatic bladder cancer tissues compared to primary tumor tissues, and its expression positively correlated with advanced clinical stages and poor prognosis in patients. In vitro and in vivo experiments demonstrated that YWHAG knockdown significantly reduced the invasive, metastatic, and colonization capabilities of bladder cancer cells. Transcriptome analysis revealed that YWHAG knockdown markedly inhibited the phosphorylation of ERK1/2 (extracellular signal-related kinases 1 and 2) and JNK (JUN N-terminal kinases), key components of the MAPK (mitogen-activated protein kinase) signaling pathway. Mechanistically, YWHAG was found to promote bladder cancer cell invasion and metastasis by regulating TMOD3, which subsequently activates the MAPK pathway. Conclusion YWHAG upregulates TMOD3 expression, leading to the activation of ERK1/2 phosphorylation in the MAPK pathway, thereby promoting the invasion and metastasis of bladder cancer cells.